2011
DOI: 10.4103/2152-7806.85986
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pineal chordoma

Abstract: Background:Chordomas are rare tumors that arise from the remnants of embryonic notochord anywhere along the neuroaxis. Even though they may occur in an extraosseous intradural location, the most common sites include the sacrococcygeal and clivus regions. The authors report a unique presentation encompassing the pineal region with metastasis to the peritoneum after a ventriculoperitoneal (VP) shunt procedure and review the current knowledge about their pathophysiology and management. The presentation and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…23 The last way of seeding is along a ventriculoperitoneal shunt; one case of pineal CH treated by radiotherapy and ventricular shunt was diagnosed after a seeding in the abdomen. 55 …”
Section: Treatment Modalitiesmentioning
confidence: 97%
“…23 The last way of seeding is along a ventriculoperitoneal shunt; one case of pineal CH treated by radiotherapy and ventricular shunt was diagnosed after a seeding in the abdomen. 55 …”
Section: Treatment Modalitiesmentioning
confidence: 97%
“…It was a pineal chordoma with abdominal metastasis, due to previous ventriculoperitoneal shunt placement. The origin of such intraparenchymal tumours is not clear and it has been suggested that they arise from ecchordosis physaliphora (EP) or directly from notochord remnants that subsist within brain tissue [8,10]. The cases described suggest ectopic notochordal remnants may be located in different areas, even away from the neuroaxis.…”
Section: Discussionmentioning
confidence: 82%
“…The first case of an intracerebral hypothalamic chordoma was reported by Commins et al in 1994 [8]. The second case has been recently described by Figueiredo et al [10]. It was a pineal chordoma with abdominal metastasis, due to previous ventriculoperitoneal shunt placement.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…15,16 Interestingly, multiple reports concern unusual presentations in youngsters, such as: extra clival cranial, intra cerebral, mediastinal, gluteal, etc. [17][18][19][20][21][22][23][24][25][26][27][28][29] Symptoms at presentation depend on the tumor site, and are not specific to children. If they are IC, cranial nerve palsies are seen in 60% or so.…”
Section: Review Of Literaturementioning
confidence: 99%